ФИЗИКА ЎҚИТУВЧИСИНИНГ ТАЪЛИМГА ИННОВАЦИОН ЁНДАШУВИ (Scientific journal of the Fergana State University, 2023)
This article is devoted to learn innovation problems in education to create virtual labs using educational software.